John Bunyan and Covenant Thought in the Seventeenth Century - Greaves, Richard Lee (Church history, 1967)
For a man who had achieved deserved fame as a master of English allegory and had thereby become the subject of a host of biographies, Bunyan would be dismayed if he knew that, three hundred years after his initial if temporary release from the Bedford prison, the thing he had strived for most in his writings had been ignored—his attempt to clarify for his readers what he believed to be the central truths of the Christian faith. Historians have diligently sought for every piece of evidence available to fill in the unknown facts of Bunyan's life, while scholars of English literature continue to examine the style of writing of the unlettered Tinker. Yet no one has ever dealt satisfactorily with the thought of this man.